The Relationship between Work Period and Dust Level with Disruption of Lung Capacity in Asphalt Mixing Plant Production Workers (AMP) Medan in Public Works Office 2019 - Dinda Sekar Mentari; Taufik Ashar; Nurmaini Nurmaini (Britain International of Exact Sciences (BIoEx) Journal, 2020)
One of the most potent sources of air pollution is from the industrial sector. The air pollutants produced from the industry are TSP dust. Long exposure for a long time can pose a risk in the form of impaired pulmonary function capacity. The purpose of this study was to find out the relationship between years of work, dust levels with impaired lung capacity in the environment of hot mix asphalt production officers in the Public Works Office of Medan City. This type of research is observational analytic with a cross-sectional design. A sample of 45 workers in the hot mix asphalt production section in the AMP area of the Medan City Public Works Service. The results of the study found that the dust levels in AMP were still below the NAB, ranging from 2-8.10 mg / m3, workers who had pulmonary function disorders were 15 people (34%). The results of the analysis using the Pearson correlation test showed that there was a moderate relationship between dust exposure and lung function capacity with a value of r = -0.432, p = 0.003, and there was a weak relationship between the work period and the function of pulmonary function with a value of r = -0.384, p = 0.009 . Therefore, it is recommended to the Public Works Office of Medan City to provide respirators for workers to prevent the excessive entry of dust into the body.